LTAD Concept Learning To Train Stage of Taekwondo Sport: Narrative Study - Nur Styasih; Sugiyanto Sugiyanto; Hanik Liskustyawati; Slamet Riyadi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
LTAD was initiated by Balyi has stages, one of which is the learning to train stage aged 8-12 years. This stage is entering the golden age and crucial, as coaches need to understand this basic concept. But some previous studies say there is still a need for information and evidence to support this concept. The purpose of this study is to provide information about the concept of LTAD learning to train taekwondo stage through literature review studies as a research method. Based on document analysis in the form of relevant articles and ebooks, the learning to train stage emphasizes self-control, respect, perfecting basic technical skills with a playful approach, developing tactical and practical knowledge and learning basic strategies for defense and attack. Develop special skills, develop speed, agility, balance, eye and hand coordination. It has begun to introduce exercise tools such as medicine balls and other tools. Emphasis on concentration, emotional control, self-confidence. Practice is about 70% and match is 30%. At this stage, the main goal is not to win, but the athlete can integrate the exercises that have been obtained. The author hopes that this study will provide information for taekwondo practitioners and academics related to the LTAD concept of learning to train. This study is only narrative, future research needs to use experimental and longitudinal methods to test the effectiveness of the LTAD concept